A Review of Direct Observation Research within the past Decade in the Field of Emotional and Behavioral Disorders. (August 2014) - Adamson, Reesha M.; Wachsmuth, Sean T.
This study reviewed prominent journals within the field of emotional and behavioral disorders to identify direct observation approaches, reported reliability tatistics, and key features of direct observation. Selected journals were systematically reviewed for the past 10 years identifying and quantifying specific direct observation systems and approaches. Suggestions for the field of special education are listed based off identified trends that existed within the past decade of literature. Implications and recommendations for research and practice are described.